Mother tongue-based Multilingual Education in Bihar: A Practical Approach - Raaj, Shilpy (IJRDO- Journal of Educational Research, 2017)
Research has shown a positive correlation between multilingual language proficiency and academic achievement by emphasising that multilingualism leads to greater cognitive flexibility and social tolerance. Some studies in India have undertaken empirical research to prove this but not much has been done in the state of Bihar despite having a rich repertoire of languages and firm language policies in place. There is a need of weaving theory with practice so that the multilingual classrooms in Bihar can actually be developed as a resource and children do not feel marginalised merely on account of language. This would go a long way in mainstreaming the linguistic minority children and preventing indigenous languages from dying out. Issues such as these provided the rationale for writing this paper which aims at bridging the gap between the policies and their actual implementation in the classrooms by giving some recommendations at the end.